I've got the following equation:

$p(j = 1 | x, \theta) = \frac{p(j=1,x | \theta)}{p(x | \theta)}$

Why does it hold? Or maybe, how do I use Bayes Theorem in this case, i.e. if we do not only have $p(j = 1 | x)$ but $p(j = 1 | x, \theta)$?


1 Answer 1


I think I found the solution.

In general we have: $$p(\theta,x,j=1) = p(j = 1 | x, \theta) \cdot p(x,\theta) \\ \Leftrightarrow \frac{p(\theta, x, j=1)}{p(x, \theta)} = p(j=1| x,\theta)$$

By using this, we get: $$p(j = 1 | x, \theta) = \frac{p(\theta, x, j=1)}{p(x,\theta)} = \frac{p(j=1,x|\theta) \cdot p(\theta)}{p(x|\theta) \cdot p(\theta)} = \frac{p(j=1,x | \theta)}{p(x|\theta)}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.